The potentially harmful excipients in prescribed medications in a Neonatal Intensive Care Unit in Kosovo and available safer alternatives - Koshi, Blerina; Grapci, Arlinda Daka; Nebija, Dashnor; Selmani, Pranvera Breznica; Morina, Rina; Crcarevska, Maja Simonoska; Dodov, Marija Glavas; Raichki, Renata Slaveska (The Turkish Journal of Pediatrics, 2022)
Medicinal products contain excipients that might be associated with toxicity in neonates. The aim of this study was to investigate the administration of medication containing potentially harmful excipients to neonates hospitalized in Kosovo and to identify the possibility of reducing neonatal exposure to these excipients through product substitution.